2022
DOI: 10.1155/2022/3550204
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene Attenuates Subarachnoid Hemorrhage-Induced Brain Injury through the SIRT1-Dependent Nrf2 Signaling Pathway

Abstract: Neuroinflammatory injury, oxidative insults, and neuronal apoptosis are major causes of poor outcomes after subarachnoid hemorrhage (SAH). Pterostilbene (PTE), an analog of resveratrol, has been verified as a potent sirtuin 1 (SIRT1) activator. However, the beneficial actions of PTE on SAH-induced brain injury and whether PTE regulates SIRT1 signaling after SAH remain unknown. We first evaluated the dose-response influence of PTE on early brain impairment after SAH. In addition, EX527 was administered to suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Previous studies have demonstrated that CIH can induce oxidative stress in the brain tissue involved in spatial memory function [24]. Pte also protects against oxidative stress injury in microglia [25], suggesting that Pte is strongly correlated with neuronal oxidative stress. Thus, proposing that Pte could be used to treat CIH is reasonable.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have demonstrated that CIH can induce oxidative stress in the brain tissue involved in spatial memory function [24]. Pte also protects against oxidative stress injury in microglia [25], suggesting that Pte is strongly correlated with neuronal oxidative stress. Thus, proposing that Pte could be used to treat CIH is reasonable.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, PTE has demonstrated its ability to attenuate brain injury induced by subarachnoid hemorrhage through the SIRT1dependent Nrf2 signaling pathway (Z. Zhang et al, 2022). Beyond neurological diseases, PTE has also shown promise in ameliorating various other diseases by modulating SIRT1.…”
Section: Sirt1mentioning
confidence: 99%